2019
DOI: 10.1097/md.0000000000018294
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intussusception associated with adenovirus infection in monozygotic twins

Abstract: Rationale: Intussusception, a common cause of intestinal obstruction in children, typically requires medical reduction. Here, we describe the case of a pair of twins who had simultaneous intussusception and were positive for fecal adenovirus—strongly indicating that adenovirus infection may be a main cause of the intussusception. Patient concerns: Two 1-year-old twin girls were brought to Cathay General Hospital one after another on the same day. Both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Three patients had different clinical conditions, such as intussusception, biliary atresia, and Kawasaki disease, which have been associated with adenovirus ( 30 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three patients had different clinical conditions, such as intussusception, biliary atresia, and Kawasaki disease, which have been associated with adenovirus ( 30 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed simultaneous intussusception and adenovirus infection in monozygotic twins (2).…”
Section: Discussionmentioning
confidence: 98%
“…While adenoviruses are a rarely reported cause of acute appendicitis in children, they are a wellrecognized cause of intussusception in infants and young children (1)(2)(3)(4). Human adenoviruses are classi ed into seven species (A-G) and 52 recognized serotypes.…”
Section: Introductionmentioning
confidence: 99%